PENINGKATAN LAJU PERTUMBUHAN SPESIFIK IKAN LELE (Clarias sp) DENGAN SUPLEMENTASI VITAMIN C PADA PAKAN - Agung Abadi; Novela W Romboisano; Yati M Lalaem; Ernawati; Intannurfemi B Hismayasari; Asthervina W Puspitasari; Saidin (Journal of Fish Nutrition, 2022)
This study aims to determine the effect of vitamin C supplementation at feed on the specific growth rate (SGR) and Body weight Index (BWI). The high production of catfish requires increased growth. This research was conducted by adding vitamin C to the feed at 200 mg/L (A), 400 mg/L (B), 600 mg/L (C) and Control (K). The addition of vitamin C to feed conducted by dissolving vitamin C in water and then adding it to the feed according to the dose. The results of ANOVA data analysis using SPSS 16 showed that there was no significant difference sig>0.05 with values ​​for the Specific Growth Rate (SGR) respectively B 5.41 %bw/d, C 4.90 %bw/d, A 2.41% bw/d, and K 1.69 %bw/d, as well as BWI values ​​of B 89%, C 86%, A 62% and K 45%, respectively. Statistical supplementation of vitamin C in feed did not have a significant effect on increasing the specific growth rate and the percentage of weight gain index.